2016
DOI: 10.1051/e3sconf/20160703010
|View full text |Cite
|
Sign up to set email alerts
|

River Loire levees hazard studies – CARDigues’ model principles and utilization examples on Blois levees

Abstract: Abstract. $ORQJ WKH ULYHU /RLUH LQ

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…For central Loire levee systems, we naturally reused CARDigues tool [15] and adapted it to above presented methodology. [15] Indeed, CARDigues tool was used on 46 Loire levees hazards studies and geometry data (shown on Figure 7) are already imput for each representative profile of levee segment, every 50 ml length (generally). Presence and nature of reinforcements are also available data.…”
Section: Evaluation Tool To Evaluate Structural Levee Costmentioning
confidence: 99%
See 1 more Smart Citation
“…For central Loire levee systems, we naturally reused CARDigues tool [15] and adapted it to above presented methodology. [15] Indeed, CARDigues tool was used on 46 Loire levees hazards studies and geometry data (shown on Figure 7) are already imput for each representative profile of levee segment, every 50 ml length (generally). Presence and nature of reinforcements are also available data.…”
Section: Evaluation Tool To Evaluate Structural Levee Costmentioning
confidence: 99%
“…Figure 2. Description of the levee system separation in representative levee segments and profiles(Durand E., 2016) …”
mentioning
confidence: 99%